A study of self-efficacy and health promoting behaviour among older adult with chronic illness / Maznah Ibrahim ...[et al.] - Ibrahim, Maznah; Damanhuri, Nur Farzana; Razak, Puteri NurFarah Hanan (2018)
Chronic illness is the largest cause of death worldwide. Number of chronic illness increase along with the increasing number of older adult. Approximately 85 percent of older adults have at least one chronic illness. Recently, self-efficacy has been recognized as an important element that has contribute to the improving health promoting behaviour among older adult with chronic illness. Self-efficacy was an individual belief to do certain task or behaviour. The aim of this study were to identify level of self-efficacy and level of health-promoting behaviour also the relationship to the demographic data. Subsequent to this, relationship between self-efficacy and health promoting behaviour was investigated. A cross-sectional study has been conducted using a questionnaire which consists of demographic data, General self-efficacy scale (GSES) and health promoting lifestyle profile (HPLP II) that were distributed to the 218 participant at UiTM Medical Specialist Centre. The participants were older adult age 60 and above that has at least 1 chronic illness. The results showed high level of selfefficacy (mean=30.6) and moderate level of health promoting behavior (mean=149.07). Subscale interpersonal relationship has the highest level among participants which (mean=27.91). Surprisingly, subscale physical activity was the lowest (mean=18.41) indicated that older adult do not have motivation to exercises due to chronic illness. Based on the findings, both self-efficacy and health promoting behaviour do not correlate with demographic data. Relationship between self-efficacy and health promoting behaviour was analyzed using spearman correlation revealed that there was a correlation between self-efficacy and health promoting behaviour at (rho =0.28, p = 0.001). This study indicated that level of self-efficacy will greatly influence the health promoting behaviour of older adult. It is hoped that this research can benefits health practitioner in managing and treating chronic illness patients. Future research is recommended to identify factor that increase self-efficacy because self-efficacy plays an important role in behaviour change in ourselves.